Solar PVT-assisted high-temperature CO2 heat pump with thermal storage: Design for net-zero electricity operation and ethical sustainability - Yuan Ma; Yaxiong Wang; Yu Ma; Ziyang Cheng; Di Zhong (PLoS ONE, 2026)
To build a clean, low-carbon and efficient energy utilization system, solar photovoltaic–thermal (PVT) assisted heat pump technologies are promising for supplying high-temperature heat in industrial sectors and accelerating the green transition of the energy system. By targeting net-zero daily electricity use and reduced reliance on fossil fuels, such systems can also support ethically sustainable industrial process heat. In this study, a solar PVT-assisted high-temperature CO 2 heat pump system with a hot-water storage tank is proposed and analyzed. The PVT field simultaneously generates electricity to drive the compressor and recovers photovoltaic waste heat to charge the thermal storage, which serves as the low-temperature heat source of a transcritical CO 2 heat pump. This work presents a dynamic co-design of an integrated PVT-storage-heat-pump system to achieve net-zero daily electricity operation, with explicit consideration of ethical sustainability in industrial heat supply. A dynamic mathematical model is developed and applied to a typical meteorological day in Xi’an, China, to provide 10 kW continuous heat above 100 °C over 24 h. The effects of the number of PVT modules, storage tank volume and initial storage temperature on system behavior are investigated. Results show that at least 32 PVT modules are required to guarantee 24 h stable operation, with the storage temperature and heat pump COP (Coefficient of performance) exhibiting a decrease–increase–decrease trend throughout the day; as the initial storage temperature increases from 25 °C to 50 °C, the average COP rises from 3.59 to 4.37. For a given number of PVT modules, the net daily electrical output increases with storage volume and significantly increases with the initial storage temperature, varying from −6.06 kWh to 2.32 kWh within the investigated range, and reaching its maximum at a storage volume of 5 m³ and an initial temperature of 50 °C. A storage volume of 4.4 m³ and an initial temperature of 42 °C yield a net daily electrical output of approximately zero, i.e., the electricity generated by the PVT field fully compensates the compressor consumption. Under this self-sufficient condition, the maximum instantaneous electrical efficiency gain of the PVT modules compared with a standalone PV array is 5.03%, while the maximum hourly PVT electrical output and net electrical output reach 5.91 kWh and 3.43 kWh, respectively.